2001
DOI: 10.1007/bf03030350
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of grape (Vitis labruscana cv. Kyoho) by shoot-tip culture

Abstract: We investigated the optimal levels of growth regulators, culture media, and pH on callus growth and organogenesis of in-vitro cultured 'Kyoho' grapes. Calli were induced by culturing leaf blades on an MS basal medium supplemented with 1 mg/IL BA and 0.01 mg/L 2,4-D. In addition, calli originating from the exocarp and mesocarp of grape fruits developed on MS media supplemented with 0.1 mg/L IAA, NAA, or 2,4-D, or with 0.2 mg/L BA. In testing the potential for plant regeneration from shoot tips on various media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Nevertheless, there was no clear relationship between the concentration of BAP and the callus intensity. This could indicate that this response might be influenced by other factors (e.g., physiological state or nodal stem localization) related to the endogenous level of the plant growth regulators (PGRs) in the plant tissue [61,62].…”
Section: Induction Of Axillary Bud Developmentmentioning
confidence: 99%
“…Nevertheless, there was no clear relationship between the concentration of BAP and the callus intensity. This could indicate that this response might be influenced by other factors (e.g., physiological state or nodal stem localization) related to the endogenous level of the plant growth regulators (PGRs) in the plant tissue [61,62].…”
Section: Induction Of Axillary Bud Developmentmentioning
confidence: 99%
“…The combination of various growth regulators and their concentrations significantly influences shoot length due to their effect on cell division and cell expansion (Gordon and Letham, 1975). Therefore, growth regulators are noticeably important for in vitro shoot proliferation, but some internal factors and nutrient conditions can modify their activities (Park et al, 2001). Shoot regeneration also depends upon endogenous levels of growth regulators in the explant and the position of node, as different types of buds showed different regeneration efficiencies in grape (Nontaswatsri et al, 2002).…”
Section: Growth Of In Vitro Shoot Culturesmentioning
confidence: 99%
“…Many studies have reported that rootstock varieties reveal higher organogenesis and somatic embryogenesis potential than hybrids and varieties belonging to the V. vinifera species [133]. However, several other factors were reported to influence the efficiency of grapevine in vitro plant regeneration, such as culture medium composition, especially the type and concentrations of plant growth regulators (PGRs) [134,135]; explants' developmental stage [136] and phyllotactic position [137]; light regime [138]; pH value [139], etc. Therefore, over the years, numerous studies were focused mainly on optimizing protocols for efficient regeneration across different grapevine genotypes.…”
Section: Grapevine Plant Regeneration Methodsmentioning
confidence: 99%